2018
DOI: 10.3847/1538-4357/aad005
|View full text |Cite
|
Sign up to set email alerts
|

Highest Frequency Detection of FRB 121102 at 4–8 GHz Using the Breakthrough Listen Digital Backend at the Green Bank Telescope

Abstract: We report the first detections of the repeating fast radio burst source FRB 121102 above 5.2 GHz. Observations were performed using the 4−8 GHz receiver of the Robert C. Byrd Green Bank Telescope with the Breakthrough Listen digital backend. We present the spectral, temporal and polarization properties of 21 bursts detected within the first 60 minutes of a total 6-hour observations. These observations comprise the highest burst density yet reported in the literature, with 18 bursts being detected in the first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
273
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 299 publications
(311 citation statements)
references
References 33 publications
(50 reference statements)
25
273
3
5
Order By: Relevance
“…In a large sample of FRB 121102 bursts detected within 4 hours, Gajjar et al (2018) and Zhang et al (2018) found bursts to occur at preferred frequencies in their 4 − 8 GHz band. We show that this behaviour is present at 1.4 GHz as well (Figure 3).…”
Section: Burst Spectramentioning
confidence: 98%
See 1 more Smart Citation
“…In a large sample of FRB 121102 bursts detected within 4 hours, Gajjar et al (2018) and Zhang et al (2018) found bursts to occur at preferred frequencies in their 4 − 8 GHz band. We show that this behaviour is present at 1.4 GHz as well (Figure 3).…”
Section: Burst Spectramentioning
confidence: 98%
“…The detection of a large sample of bursts from FRB 121102, at observing frequencies ranging from 1 to 8 GHz (e.g. Spitler et al 2016;Scholz et al 2016;Law et al 2017;Michilli et al 2018a;Gajjar et al 2018;Spitler et al 2018;Zhang et al 2018;Hessels et al 2019), has led to a variety of observed spectra. For instance, they cannot be consistently described by a single spectral index, some bursts exhibit a frequency dependent profile evolution, and burst spectra from Law et al (2017) are typically limited to 500-MHz wide Gaussian envelopes.…”
Section: Introductionmentioning
confidence: 99%
“…We postpone the spectrum modelling to future work, when a wider frequency coverage is available. The flat-spectrum assumption is driven by the repeater FRB 121102, for which an apparently flat spectrum with ∼ 1 GHz bandwidth was observed (Gajjar et al 2018).…”
Section: The Measurementsmentioning
confidence: 99%
“…It is firmly established that at least a few milli-second duration, very bright, radio signals that have been detected between about 400 MHz and 7 GHz (known as Fast Radio Bursts or FRBs) are coming from a distance of about a Gpc or more, eg. Lorimer et al 2007; Thornton et al 2013;Spitler et al 2014;Petroff et al 2016;Bannister et al 2017;Law et al 2017;Chatterjee et al 2017;Marcote et al 2017;Tendulkar et al 2017;Gajjar et al 2018;Michilli et al 2018;Farah et al 2018;Shannon et al 2018;Oslowski et al 2019;Kocz et al 2019;Bannister et al 2019;CHIME Collaboration 2019a and2019b;Ravi 2019aRavi , 2019bRavi et al 2019. Many mechanisms have been suggested for the generation of high luminosity coherent radio waves from Fast Radio Bursts (FRBs), eg. Katz (2014Katz ( , 2016, Murase et al (2016;, Kumar et al (2017), Metzger et al (2017), Zhang (2017), Beloborodov (2017), Cordes (2017), Ghisellini & Locatelli (2018), Lu & Kumar (2018), Metzger et al (2019), Thompson (2019), Wang & Lai (2019), ; for a recent review see Katz (2018).…”
Section: Introductionmentioning
confidence: 99%